Geodetic Constraints on the Qinghai-Tibetan Plateau Present-Day Geophysical Processes - Kamil Erkan; C. K. Shum; Lei Wang; Junyi Guo; Christopher Jekeli; Hyongki Lee; Wendy R. Panero; Jianbin Duan; Zhenwei Huang; Hansheng Wang (Terrestrial, Atmospheric and Oceanic Sciences, 2011)

(untitled)
The Qinghai-Tibetan Plateau is the largest and the highest area in the world with distinct and competing surface and subsurface processes. The entire Plateau has been undergoing crustal deformation and accompanying isostatic uplift as a result of the Cenozoic collision of the Indian and Eurasian continents. Regional secular surface mass changes include the melting of mountain glaciers and ice caps, and permafrost layer degradation due to global warming. There is also a plausible effect of glacial isostatic adjustment due to the removal of a possible Pleistocene ice-sheet. In this article, we present an assessment of the sizes and extents of these competing interior and exterior dynamical processes, and their possible detections using contemporary space geodetic techniques. These techniques include, in addition to GPS, satellite radar altimetry over land, and temporal gravity field measurements from the Gravity Recovery and Climate Experiment (GRACE) satellite mission. These techniques are complementary: land satellite altimetry, similar to GPS, is sensitive only to surface uplift, whereas GRACE is sensitive to both surface uplift and mass changes inside the Earth. Each process may dominate the others in a particular region. Our analysis shows that GRACE data are more sensitive (than GPS or land altimetry) to hydrologic and meteorology signals, some of which are larger than the combined effect of geodynamic processes and permafrost degradation.